Enhancement of Thermophilic Digestion of Food Waste (FW) via Trace Element Supplementation - Duygu Karaalp; Tugba Keskin; Kubra Arslan; Nuri Azbar (Journal of Chemical Engineering Research Updates, 2019)
In this study, the role of trace element (TE) supplementation and performance characteristics of a thermophilic anaerobic digester fed by food wastes (FW) is investigated in the long run, and a representative operational data set for field application is reported over the whole experimental period. Continuous feeding of food wastes with a dry matter of 5% for 150 days was carried out using a 100 L pilot-scale CSTR type anaerobic digester under thermophilic operation conditions. Hydraulic retention time (HRT) and organic loading rate (OLR) were kept around 28 days and less than 3.0 kg oDM m3 day-1, respectively. Volumetric biogas production values were reported to be 0.32 m3 m-3 day-1 during the period where there is no TE supplementation; on the other hand, biogas production was doubled (0.69 m3m-3day-1) following TE supplementation. This corresponds to an average unit biogas production of 317 and 443 L kg-1 oDM, during TE supplementation and no TE supplementation periods, respectively. Statistical analysis indicated that Co, As, Se, and Al were the most significant trace elements affecting the digester performance.